The adoption of an electronic booking (E-booking) system for the container booking process in the maritime supply chain - Zeng, F (2021)
Information systems (IS) have been playing increasingly crucial roles in supporting the smooth running of maritime supply chain operations. Inter-organisational information systems (IOIS) have been suggested for use in this context to increase data visibility and working efficiency. However, the degree of acceptance of such systems within the maritime servicing chain remains varied, and the overall adoption rate is low, which motivated this research. This study aims to understand the adoption of IOIS in the form of container e-booking systems by organisations in the maritime supply chain, from three aspects: the actual container booking process, the factors affecting the adoption intention of organisations in the maritime supply chain, and the different extents of the impact of the factors identified over organisations across multiple tiers in the chain.